In vitro evaluation of imidazo[4, 5-c]quinolin-2-ones as gametocytocidal antimalarial agents. Issue 12 (15th June 2016) - Patel, Paresma R.; Sun, Wei; Kim, Myunghoon; Huang, Xiuli; Sanderson, Philip E.; Tanaka, Takeshi Q.; McKew, John C.; Simeonov, Anton; Williamson, Kim C.; Zheng, Wei; Huang, Wenwei
Graphical abstract: Abstract: Novel imidazo[4, 5- c ]quinolin-2-ones were synthesized and evaluated in asexual blood stage and late stage gametocyte assays of Plasmodium falciparum, a major causative agent of malaria. The design of these compounds is based on a recently identified lead compound from a high throughput screen. A concise synthesis was developed that allowed for generation of analogues with substitution around both the quinoline and imidazolidinone rings. Through structure–activity relationship studies, a number of potent compounds were identified that possessed excellent antimalarial activity against both the asexual and sexual stages with minimal cytotoxicity in mammalian cells. This is the first Letter describing SAR and gametocytocidal activity of imidazo[4, 5- c ]quinolin-2-ones, a new lead series for malaria treatment and prevention.